Well-Being–Based Early Childhood Education for Trauma Recovery: A Phenomenological Study of Parental Perceptions - Ferawati, Ferawati (Qualitative Research in Early Childhood Education, 2026)
Student well-being and social–emotional learning (SEL) have become central issues in contemporary education, particularly in post-crisis contexts that affect children’s mental health. Early childhood education (ECE) plays a critical role in supporting children’s emotional well-being from an early age. This study aims to explore parents’ perceptions of well-being–based early childhood education in the context of post-crisis trauma recovery. A qualitative phenomenological approach was employed. Ten parents of kindergarten children living in disaster-affected areas in Aceh were selected through purposive sampling. Data were collected through structured interviews and analyzed using thematic analysis. The findings revealed four themes: ECE as a foundation for children’s emotional well-being, a shift from academic orientation to mental health, teachers as facilitators of social–emotional learning, and education as a space for family psychosocial recovery. The study shows that parents prioritize children’s emotional safety and well-being over early academic achievement. These findings highlight the importance of implementing well-being–based and trauma-sensitive approaches in early childhood education.